2019
DOI: 10.1007/s10661-019-7293-7
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic field dissipation and fate of endosulfan after application on Theobroma cacao farm in tropical Southwestern Nigeria

Abstract: benzodioxathiepin-3-oxide is still a pesticide of choice for most cocoa farmers in Southwestern Nigeria, in spite of its persistence, bio-accumulative, toxicological properties and restriction. A single-treatment of 1.4 kg ai/ha (0.5% ai) of technical grade endosulfan (Thiodan, 35EC) was applied to 0.0227 hectare of cultivated Theobroma cacao L. (Cocoa) farm at the Cocoa Research Institute of Nigeria (CRIN). Levels of parent endosulfan (α-, β-endosulfan) and major metabolite (endosulfan sulfate) were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…The modeling of GCM fills a gap in the consideration of common farming practices, and demonstrated the potential of GCM to reduce emissions to field soil and related freshwater ecotoxicity impacts. Following our proposed approach to considering GCM processes, our emission results reproduce well the effect of GC on pesticide distribution as observed in cocoa farm systems by Vaikosen et al ( 2019 ), where the reduction in bare soil surface with a GC of fallen leaves of the main crop decreased emission to the top soil. The higher the fraction of effective area of cover (composed of living or dead cover), the lower the fraction distributed to field soil.…”
Section: Discussion and Outlooksupporting
confidence: 82%
“…The modeling of GCM fills a gap in the consideration of common farming practices, and demonstrated the potential of GCM to reduce emissions to field soil and related freshwater ecotoxicity impacts. Following our proposed approach to considering GCM processes, our emission results reproduce well the effect of GC on pesticide distribution as observed in cocoa farm systems by Vaikosen et al ( 2019 ), where the reduction in bare soil surface with a GC of fallen leaves of the main crop decreased emission to the top soil. The higher the fraction of effective area of cover (composed of living or dead cover), the lower the fraction distributed to field soil.…”
Section: Discussion and Outlooksupporting
confidence: 82%
“…These findings further confirmed that the pesticides were still available in Nigeria either singly or as a mixture with other active ingredients despite their ban. A long-time accumulation of the endosulfan sulphate in soil and on plant surfaces have been reported to be due to its persistent as a major metabolite of the less persistent α - and β -endosulfan (Jack and Phil, 2004; Rosendahl et al , 2009) with a half-life 1.5 times longer than other isomers (Vaikosen et al , 2019) and this could have been one of the reasons for its high concentration in the fruit vegetables. The technical or commercial endosulfan pesticide (90–95% of the pure endosulfan mixture) is a mixture of α -endosulfan (70%) and β -endosulfan (30%) (Yu et al , 2014; Baqar et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The technical or commercial endosulfan pesticide (90–95% of the pure endosulfan mixture) is a mixture of α -endosulfan (70%) and β -endosulfan (30%) (Yu et al , 2014; Baqar et al , 2018). The lower concentrations of α-endosulfan in comparison to other isomers showed that the applied pesticides had degraded to more persistent isomers as the α-isomers are more susceptible to enzymatic breakdown or easily degraded (Yu et al , 2014; Vaikosen et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of endosulfan sulfate detected in this study were higher than the concentrations earlier reported by Sosan et al (2018) and Anzene et al (2014) on maize from Nasarawa State, Nigeria. The higher concentrations of endosulfan sulfate could be due to volatilization and degradation of endosulfan (αand β-isomers) present on the maize grains to a more persistence endosulfan sulfate leading to its increase in concentration, as the endosulfan (α-and β-isomers) are easily degraded with shorter half-life on plant and soils (Vaikosen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%